Transtorno do espectro autista: a prática com ênfase nas políticas públicas educacionais inclusivas - HERNANDES , Camila Martins (2021)
This dissertation is linked to the research line “Public Policies in Education, Formative Processes and Diversity” of the Graduate Program in Education at the University of Oeste Paulista (PPGE/UNOESTE). The general objective of the research was to: Analyze, in the context of the Regular Teaching Network and in Special Education, how teachers understand what Inclusive Education is and the educational public policies regarding the inclusion of people with Autistic Spectrum Disorder (ASD) , and how they are put into practice. The investigation was of a qualitative nature, of the case study type, and involved a private school from the Regular Teaching Network and a Special School, in a medium-sized city in the interior of the state of São Paulo. The research was submitted and approved by the Research Ethics Committee (CEP), approved with the Certificate of Presentation of Ethical Appreciation (CAAE) 39973320000005515. Three (03) teachers from each school, who have in their classes participated in the study students who are within the autistic spectrum, totaling six (06) teachers. Two (02) pedagogical coordinators also participated in the survey, one (01) from each school. For data collection, semi-structured interviews were conducted with the 08 participants. Data analysis follows the propositions of Bardin's content analysis technique, based on interview transcripts. The results answer the central question of the research: "has the practices of teachers in Regular Education and Special Education met the guidelines of educational policies, with regard to the development of inclusive education for students with ASD?" above all, as material for reflection and final discussion on how public policies can intervene in the quality of insertion and inclusion of children with autism.